2014
DOI: 10.1590/s1516-89132014005000014
|View full text |Cite
|
Sign up to set email alerts
|

Scale up of production in a bioreactor of a halotolerant protease from moderately halophilic Bacillus sp. isolated from soil

Abstract: Studies were conducted on the production of protease by moderately halophilic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The bacterium was isolated from poultry soil and was identified as Bacillus sp. MTCC 9558 belonging to B. cereus cluster was found to be a good producer of protease reported by us earlier (Prasad et al 2014).…”
Section: Microorganismsupporting
confidence: 58%
“…The bacterium was isolated from poultry soil and was identified as Bacillus sp. MTCC 9558 belonging to B. cereus cluster was found to be a good producer of protease reported by us earlier (Prasad et al 2014).…”
Section: Microorganismsupporting
confidence: 58%
“…The study of NA7 growth kinetics with reference to protease production demonstrated that, prior to the end of the exponential phase, the culture showed marked protease production efficiency with relatively stable maximum activity records (0.610-0.625 TU) for more than 60 h during the stationary phase. When compared to other similar halotolerant Bacillus shake flask condition (Prasad et al, 2014), the expression phase of the proteolytic activity is very much longer.…”
Section: Discussionmentioning
confidence: 88%
“…The refractive index obtained is 1.3381 so the concentration of ethanol was 8 % w/w. Agro-based byproducts as being used as an alternate substrate for the commercial production of several industrially important products [9]. Based on the type of feedstock used, industrial bioethanol production is divided into three generations and approximate ethanol yields from different types of feedstocks have been studied extensively [10].…”
Section: Concentration Of Ethanolmentioning
confidence: 99%